Analysis of CT Number Value According To Tube Voltage by CT Equipment Manufacturer - Kim, Jung-Hoon; KiKim, Seon; Lim, Cheong-Hwan (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study is to provide the basic data for imaging by analyzing the difference of a CT number according to the set energy of each CT equipment manufacturer.Methods/Statistical analysis: In this study, the CT equipment analysis is targeted at the equipment manufactured by Siemens, GE, Canon, and Philips. In this reference, the phantom used by the Nuclear Associates 76-410 CT phantom and its own phantom. Here, the tube exposure was fixed at 250mAs, while the exposure conditions were changed to 140Kv, 120Kv, 100Kv and 80Kv. In this case, the experiment was repeated twice, and the CT number of the material was measured and analyzed with the same size regions of interest (ROI) in each phantom image.Findings: The results showed that the CT number of the material was found to decrease, as the tube voltage decreased in all five materials of AAPM. Additionally, when the same tube voltage was set, the GE equipment showed the lowest CT number values for all five AAPM materials. It is noted that in the self-made 6% contrast agent phantom, the CT number increased gradually as the tube voltage decreased. Finally, when the same tube voltage was set, the Siemens equipment showed the lowest CT number in this case.Improvements/Applications: The prevailing discipline in this study noted that when medical institutions use CT numbers to read or measure images, it is necessary to identify and utilize the range of variation in the CT number of the material, and calculate that number according to the tube voltage of the equipment being used. In particular, it is considered that these results are significant, and the calibrations noted should be used for the determination of patient diagnosis with a different range of criteria for each manufacturer, whereby the active CT number correction is also necessary to be performed in each case with the different equipment being utilized for CT evaluation for patient health outcomes.